Analisis Resepsi Rasisme dalam Video Klip Lagu “This is America” terhadap Penonton Multi Etnis (Universitas Negeri Surabaya, 2022)
Analysis of multi-ethnic audience reception of racism in the video clip of the song This is America. This study aims to determine how the audience's reception of racism in the video clip of the song This is America. In the video clip of the song This is America contains scenes that are full of violence. When the MV for this song was released, there were various reactions and controversies. By using qualitative research methods data obtained through interviews and observations. Then the data analysis technique is divided into three steps, data reduction, data presentation and drawing conclusions. Based on the theory of encoding - decoding, the position of the audience is divided into three, dominant hegemonic, negotiating and opposition. The results of the study show various reactions and opinions from multi-ethnic audiences towards racism in the video clip of the song. With the opinion of each audience, it is concluded that their position is in a dominant and negotiating hegemonic position.